The Potential of Mangifera indica L. Peel Extract to Be Revalued in Cosmetic Applications - Abigail García-Villegas; Álvaro Fernández-Ochoa; Alejandro Rojas-García; María Elena Alañón; David Arráez-Román; María de la Luz Cádiz-Gurrea; Antonio Segura-Carretero (MDPI AG, 2023)
The constant growth of the cosmetic industry, together with the scientific evidence of the beneficial properties of phytochemicals, has generated great interest in the incorporation of bioactive extracts in cosmetic formulations. This study aims to evaluate the bioactive potential of a mango peel extract for its incorporation into cosmetic formulations. For this purpose, several assays were conducted: phytochemical characterization; total phenolic content (TPC) and antioxidant potential; free-radical scavenging capacity; and skin aging-related enzyme inhibition. In addition, the extract was incorporated into a gel formulation, and a preliminary stability study was conducted where the accelerated (temperature ramp, centrifugation, and heating/cooling cycles) and long-term (storage in light and dark for three months) stability of the mango peel formulations were evaluated. The characterization results showed the annotation of 71 compounds, gallotannins being the most representative group. In addition, the mango peel extract was shown to be effective against the •NO radical with an IC50 of 7.5 mg/L and against the hyaluronidase and xanthine oxidase enzymes with IC50 of 27 mg/L and 2 mg/L, respectively. The formulations incorporating the extract were stable during the stability study. The results demonstrate that mango peel extract can be a by-product to be revalorized as a promising cosmetic ingredient.